Seeking academic help: The case of lower secondary students with autism spectrum disorder and their teachers. (August 2022) - Zorn, Sabine; Puustinen, Minna
Abstract: Our aim was to complement results obtained using interview data (Zorn & Puustinen, 2017a) by analyzing video data on the same students' (i.e., 11 students with ASD) actual help-seeking behavior as well as their teachers' ( n  = 17) subsequent help-giving behavior, in everyday classroom situations in both general and resource class within a mainstream lower secondary school. Ten students sought help from their teachers at least once in both contexts, yet interpersonal differences were observed. Although student help seeking partly fell into "traditional" help-seeking categories (i.e., instrumental help seeking, confirmation-asking), new help-seeking categories also emerged (i.e., ambiguous and organizational help seeking). Students always used verbal means to solicit help; in addition, both nonverbal and verbal means to draw teachers' attention were identified. More than 70% of help giving consisted of providing direct feedback, explaining, or instructing. The importance of analyzing the help-seeking process in an ecologically valid context is emphasized. Highlights: Most students with ASD sought help from their teacher in general and resource class. Observation data only partially corroborated results obtained using interview data. New help-seeking categories–unspecified and organizational help seeking–emerged. Students expressed their request by formulating a question or making a statement. Most teachers responded by providing direct feedback, explaining, or instructing.